Patagonia : driving sustainable innovation by embracing tensions - O'Rourke, Dara; Strand, Robert (London : SAGE Publications Ltd, 2017)
This case study examines the tensions that arise when Patagonia simultaneously pursues sustainability and quality objectives embedded within its mission statement to build the best product, cause no unnecessary harm, use business to inspire and implement solutions to the environmental crisis. Specifically, this case study focuses on Patagonias Durable Water Repellent (DWR) problem--DWR is a highly effective chemical treatment used to waterproof jackets (supporting the quality objective) but has by-products that are toxic and persist in the environment (undermining the sustainability objective). This case presents Patagonias (and the industrys) challenges, its history trying to resolve the problem, including research, its temporary solution to use a less harmful but less effective option in C6, and its investment in Beyond Surface Technologies through $20 Million & Change, amongst others. The case also discusses external issues such as competitors and their efforts, pressure from Greenpeace, governmental involvement, and chemical industry actions. At the higher level, the case focuses on the question of how companies like Patagonia drive innovation down the supply chain to chemical and material suppliers, as well as how they think about innovation/disruption across the entire system, all the while grappling with internal tensions between performance, durability, and their commitment to cause no unnecessary environmental harm.
Originally published: ORourke, D., & Strand, R. (2016). Patagonia: Driving sustainable innovation by embracing tensions. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Patagonia; Clothing trade -- United States -- Case studies; Water repellents -- Technological innovations -- Case studies; Surfaces (Technology) -- Case studies